'Only by learning how to live together differently can we live together at all': readability and legibility of Central Asian migrants' presence in urban Russia. Issue 2 (2nd April 2016) - Nasritdinov, Emil
ABSTRACT: This paper questions the effectiveness and usefulness of the Russian government's policies of migrant integration. Using a unique combination of ethnographic research methods (observations, interviews and survey) with methods from psychology (cognitive mapping) and urban studies (GIS mapping), I depict the presence of Central Asian migrants and their interaction with local long-term residents in two cities of the Russian Federation: Kazan and Saint Petersburg. On the basis of my findings, I argue that the readability (defined as the ease with which the city can be 'read' and understood) and legibility (defined as the degree to which individual components of an urban environment are recognizable by their appearance) of urban space in Kazan have positive effects on the relationship between these two communities, while the ambiguity and uncertainty of urban identity in Saint Petersburg make the life of migrants very vulnerable and unpredictable, and result in the growth of xenophobic views among the local residents. This allows me to argue that the policy of migrant integration will be more successful if it is built on learning to live with differences, instead of trying to 'Russify' migrants or create various forms of supra-ethnic identity.